2006
DOI: 10.1007/s11158-006-9015-6
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy, free speech and automatic behaviour

Abstract: One of the strongest defences of free speech holds that autonomy requires the protection of speech. In this paper I examine five conditions that autonomy must satisfy. I survey recent research in social psychology regarding automatic behaviour, and a challenge to autonomy is articulated. I argue that a plausible strategy for neutralising some of the autonomy-threatening automatic responses consists in avoiding the exposure to the environmental features that trigger them. If this is so, we can good autonomy-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Thus, more balanced and nuanced entries may get lost in the feeds in favor of passionate entries by users who make use of social media as a way to satisfy an expressive interest. For people who have passionate opinions or feelings, trying to convince others of the validity of their views may become a matter of personal and moral integrity (Moles, 2007). Individuals who come to more strongly oppose out-group parties and their supporters may be more drawn to social media as a venue that allows them to realize an expressive need.…”
Section: Theory 2: Polarization Affects Social Media Usementioning
confidence: 99%
“…Thus, more balanced and nuanced entries may get lost in the feeds in favor of passionate entries by users who make use of social media as a way to satisfy an expressive interest. For people who have passionate opinions or feelings, trying to convince others of the validity of their views may become a matter of personal and moral integrity (Moles, 2007). Individuals who come to more strongly oppose out-group parties and their supporters may be more drawn to social media as a venue that allows them to realize an expressive need.…”
Section: Theory 2: Polarization Affects Social Media Usementioning
confidence: 99%
“…The view I defend in the next three chapters has a passing resem blance to a more familiar position, one I used to endorse myself. This position is also sometimes offered in response to worries about ep i ste mic paternalism, and holds that Enlightenment ideals of intellectual autonomy are psychologically unrealistic; instead paternalistic measures must take up the slack (Conly 2013;Levy 2012;Moles 2007). This famil iar response appeals to the rationality deficit view of ourselves we out lined in Chapter 1, according to which contemporary psychology has shown that rationality is a scarce resource and that for the most part we respond relatively unthinkingly.…”
Section: Dare To Think?mentioning
confidence: 99%
“…111‐2; Chambers, 2021; cf. Moles, 2007); by their lack of the epistemic virtue of ‘accuracy’, which involves ‘making a goodwill effort to find out what is true or to acquire true belief’ (Chambers, 2021, p. 159); and by a social media infrastructure that facilitates fake news's rapid diffusion, with uncertain norms over whether sharing messages implies endorsing them (Rini, 2017). Similarly, by exploiting cognitive biases, fake news seems to disrespect individual autonomy.…”
Section: New Challengesmentioning
confidence: 99%